Morbidity of multiple bowel resection compared to single bowel resection after debulking surgery for ovarian cancer. (September 2019) - Tozzi, Roberto; Casarin, Jvan; Baysal, Ahmet; Pinelli, Ciro; Matak, Luka; Ghanbarzadeh, Nahid; Alazzam, Moiad; Garruto-Campanile, Riccardo; Majd, Hooman Soleymani; Kilic, Yakup; Morotti, Matteo
Abstract: Objectives: To assess the impact of multiple bowel resections on postoperative outcomes in stage IIIC-IV ovarian cancer (OC). Methods: From the Oxford OC database we retrieved consecutive patients who underwent bowel resection between January 2009 and November 2017. Patients were divided into two groups: single bowel resection (SBR) and MBR (≥2 bowel resections). The following outcomes were compared between the two groups: 30-day related and not related morbidity to bowel surgery, bowel diversion rate and time to start/restart adjuvant chemotherapy. Results: Thirty-five patients were in the MBR and 146 in the SBR group. The 30-day overall surgical-related complication and bowel specific complications rate was higher in MBR group than SBR group (54.3% vs. 23.9%, p < 0.001) and (25.7% vs. 10.5%, p = 0.035), respectively. The rate of bowel diversion was 97.7% in MBR vs. 26.7% in the SBR group (p = 0.021). Trend analysis showed a significant reduction in the rate of MBR after the introduction of NACT (p- for trend <0.001). Conclusions: Our data show that MBR during OC surgery is associated with a higher rate of overall and bowel specific complication compared to SBR. The introduction of NACT is associated with a reduced rate of MBR.